The use of a fast method for recording schroeder-phase masking functions to estimate cochlear phase curvature - Rahmat, Sarah; O'Beirne, Greg A. (The Mediterranean Society of Otology and Audiology, 2015)

(untitled)
Until relatively recently, the influence of signal phase on human perception has largely been disregarded. However, findings in the last 20 years have shown that altering the phase characteristics of Schroeder harmonic complexes changes their ability to mask other sounds (Kohlrausch & Sander, 1995).The difference in masking produced by different phases of Schroeder complexes is thought to be contributed by the interaction between the phase curvature of the auditory filter and nonlinear cochlear processing. Our aim in this study was to demonstrate the potential use of our newly developed fast method for recording Schroeder-phase masking functions to estimate basilar membrane phase curvature. Schroeder-phase masking functions at 75 dB A masker level were recorded in six normal-hearing participants for 250 Hz, 500 Hz, 1000 Hz, and 2000 Hz using various fundamental frequencies and numbers of masker components. Cochlear phase curvature was estimated from the location of minima in Schroeder-phase masking functions. The estimated auditory filter phase curvature was negative at all tested frequencies, and approached zero as frequency increased. Scaling symmetry was not exhibited for frequencies <500 Hz. Phase curvature estimates at low frequencies contradicted estimates from animal studies, but were consistent with previous Schroeder-phase masking studies in humans (Kohlrausch & Sander, 1995; Oxenham & Dau, 2001; Lentz & Leek, 2001), indicating significant interspecies differences. Our findings suggest that the newly developed fast method of Schroeder-phase masking, with its 80% reduction in test time, may be a useful tool for psychophysical estimation of auditory filter phase curvature.